The impact of multimarket contacts on bank stability in Vietnam. Issue 3 (3rd May 2019) - Le, Tu DQ; Tran, Son H.; Nguyen, Liem T.
Abstract : Purpose: The purpose of this study is to investigate the impact of multimarket contacts on bank stability in the Vietnamese banking system between 2006 and 2015. Design/methodology/approach: The system generalized method of moments proposed by Arellano and Bover (1995) is used to examine the relationship between multimarket contacts and bank stability. Findings: The findings show that multimarket contacts among Vietnamese commercial banks improve bank stability. In addition, more x-efficient banks appear to be more stable. The same is true for banks with less holding liquid assets, for those with less excessive lending, for smaller banks, for those with the greater level of intermediation and for those with a higher level of foreign ownership. Listed banks are found to be less-risk taking than unlisted banks. Originality/value: This study is the first attempt to examine the relationship between multimarket contacts and bank stability in an emerging market in the Asia-Pacific region.